A Banking sector in India: It innovations and its Impact - Samir; Kamra, Deepa (Journal of Commerce and Trade, 2013)
The fast pace of changes in the Indian economy since liberalization; have radically and perceptibly transformed the operational environment of the banking sector. After decades of governmental safeguard for commercial banks in India, they are now exposed to an open and competitive environment. Public sector banks have now to cope with competition from both foreign and private sector banks which are equipped with superior technology, better market orientation and cost effective measures. Developments in the field of information Technology (IT) have strongly come to the rescue by infusing growth and inclusiveness into the banking sector. IT has enhanced the competitive proficiency of the Banking sector by strengthening back end administrative processes. While improvement in the front-end operations has helped in reducing the cost of operations. This paper examines the current status and varied aspects of computerisation in Public Sector and scheduled Commercial Banks for the period ended March 2005-2011 in India.